Psychological features of future psychologists’ creative potential in the context of modern educational trends - Naichuk, Victoriia; Fomenko, Karina (Personality and environmental issues, 2024)
The article is devoted to the study of psychological features of the creative potential of future psychologists in the context of modern educational trends. The study analyses the role of creative thinking in the professional activity of a psychologist and the factors that contribute to its development during studying in higher education institutions. The main components of creative potential are identified: self-control of ideas, level of immersion in the creative process, automatisation of actions, clarity of purpose, ability to think flexibly. Particular attention is paid to the analysis of the state of flow in psychology students as an indicator of the effectiveness of creative activity. In the framework of the empirical study, psychodiagnostics of students was conducted, which allowed to assess the level of development of their creative potential. It has been found that most students have a fairly high level of creative thinking, but some of them need additional support in developing the skills of a non-standard approach to solving problems. The results of the study can be used to improve educational programmes aimed at stimulating the creative activity of psychology students, in particular through the integration of interactive teaching methods, project activities and case methods.